A redox-sensitive luciferase assay for determining the localization and topology of endoplasmic reticulum proteins. - Hai-Yin Li; Xue-Ming Zheng; Mei-Xia Che; Hong-Yu Hu (PLoS ONE, 2012)
Correct localization and transmembrane topology are crucial for the proteins residing and functioning in the endoplasmic reticulum (ER). We have developed a rapid and convenient assay, based on the redox-sensitive luciferase from Gaussia princeps (Gluc) and green fluorescence protein (GFP), to determine the localization or topology of ER proteins. Using the tandem Gluc-GFP reporter fused to different positions of a target protein, we successfully characterized the topologies of two ER transmembrane proteins Herp and HRD1 that are involved in the ER quality control system. This assay method may also be applicable to the proteins in secretory pathway, plasma membrane, and other compartments of cells.